Design and implementation of multi-channel visible light communication system based on FPGA - Liu Jiehui; Gan Ruohong; Gan Zhiyu; Wang Feng; Li Ting (Dianzi Jishu Yingyong, 2023)
Compared with traditional radio frequency communication, visible light has rich spectrum resources and high security. The multi-channel visible light communication system designed in this paper is divided into transmitter and receiver. Based on Verilog HDL language, the channel distribution module, transparent framing module, channel code block segmentation module at the transmitter, transparent framing module and channel merging module at the receiver are designed in detail, and a multi-channel visible light communication system that supports 16 channels of data at the same time is realized. In order to meet the demand of the high-speed communication of the system, the transmitter / receiver circuit of visible light communication is designed and optimized, and the pre emphasis circuit is used at the transmitter to effectively compensate the channel loss. In the receiver, a T-shaped amplification circuit composed of resistance and capacitance is used to compensate the attenuated signal. Finally, the test is carried out on the experimental platform. The results show that the transmission error rate of the multi-channel visible light communication system designed in this paper is not greater than 10-9, and the single channel transmission rate is not less than 30 Mb/s. This research is conducive to improving the reliability and high speed of the visible light communication system.